Asymptomatic COVID-19 in a rehabilitation facility: evolution of the presence of nasopharyngeal SARS-CoV-2 and serological antibody responses - Harris,BHL; Zuhair,M; di,Giovannantonio M; Rosadas,C; Short,C-E; Thaventhiran,T; Quinlan,R; Taylor,A; Calvez,R; Taylor,GP; Tedder,RS; McClure,MO; et al. (The Journal of Infectious Diseases, 2021)
At the start of the UK COVID-19 epidemic, this rare point prevalence study reveals of patients in a London inpatient rehabilitation unit were found to be infected with SARS-CoV 2, but asymptomatic (n=15/45). We report on eight patients in detail, including their clinical stability, the evolution of their nasopharyngeal viral RT-PCR burden and their antibody levels over time revealing the infection dynamics by RT-PCR and serology during the acute phase. Notably, a novel serological test for antibodies against the receptor binding domain of SARS40 CoV-2 (anti-RBD) showed 100% of our asymptomatic cohort remained seropositive between 3 to 6 weeks post-diagnosis.